Determinan Akses Layanan Kesehatan bagi Orang dengan HIV/AIDS di Indonesia - Afief Mulyawijaya; Afrizal Adi Nugroho; Dinda Alsayla; Hasnadya Fathin; Anindya Nurshifa; Titik Kuntari; Benyamin Tri Dharma (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2022)
Background: HIV/AIDS is a global health problem, including in Indonesia. PLWHA's access to health services has not been evenly distributed. Only about 63% of PLWHA received initial antiretroviral therapy, 18% died, and 25.4% experienced drug withdrawal. Therefore, research is needed to determine the factors influencing the access of PLWHA to health services.Objective: This study aims to determine the factors related to access to health facilities in Indonesia for people living with HIV/AIDS (PLWHA) in Indonesia.Methods: This study uses secondary data from the 2017 IDHS. The case group was PLWHA, who had not visited a healthcare provider in the last six months. The control group was PLWHA patients who visited a healthcare provider during the last six months. The variables were the patient's and their partner's education level, types of residence, occupation, health insurance, type of health facility, and access to health facilities in the last six months. Multivariate analysis was performed by logistic regression.Results:The PLWHA access to health services was not significantly related to education level, spouse's education level, type of residence, occupation, and type of health insurance (p-value >0.05). The access is significantly related to the health facility types (OR= 4.04; 95% CI 1.173-13.955).Conclusion: The factor determining access to health services for PLWHA in Indonesia is the type of health facility. The government must make various efforts to improve the quality of facilities and services in all health facilities types to increase the number of PLWHA who undergo tests and therapy.